Building empathic connections: Playback Theatre with adolescents. Issue 2 (1st October 2020) - Reagan, Tim
Playback Theatre (PT) training with youth may be uniquely suited to enable the development of healthy pro-social behaviour amongst adolescents. In this study, 22 participants who were engaged in the Keep the Peace Leadership Program (KPLP), a PT initiative addressing themes of bullying perpetration and victimization, were interviewed about their experience. Qualitative findings were translated into an ethnodramatic play entitled Phoenix Rising to illuminate how PT fostered dialogue about different kinds of bullying.